Translating Children’s Literature in the Arab World: The State of the Art - Mdallel, Sabeur (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2003)
AbstractChildren’s literature in the Arab World is impregnated with morality, didactics and a heavy ideological bias, in spite of some attempts for change. Translating for children is, in its turn, governed by the same rules that govern writing for them.Translation is not only a lexical but also a cultural transfer. Adopting some protective cultural measures, while translating for children, becomes inevitable especially if the source and target cultures have little in common.The Arabian Nights is the first book for children in the Arab world, though not initially meant for them, to be translated into many languages and has become part of international Children’s Classics.